How Immersive Digital Technology Learning in Ecology and Environmental Education: A Systematic Literature Review - Dian Samitra; Zico Fakhrur Rozi; Reny Dwi Riastuti (FKIP Universitas Lampung, 2026)
This study investigates research trends in immersive digital technologies in ecological and environmental education. It also examines how immersive learning environments impact student learning outcomes and engagement across various educational contexts. A systematic literature review was conducted using the PRISMA protocol and the SPIDER framework. Publications were searched for between 2015 and 2025. The data obtained were analyzed descriptively. An initial search of the Scopus database identified 253 publications, and the ERIC database identified 43 publications, of which 26 studies met the inclusion criteria and were selected for in-depth analysis. The results indicate that research interest in immersive digital technologies in ecological and environmental education began in 2019. Most research on immersive digital technologies was conducted in 2025. VOSviewer analysis revealed that the identified keywords were technology, learning, and environmental substance. Among the identified technologies, virtual reality (VR) was the most dominant keyword. Furthermore, the study found that research on virtual reality technologies outnumbered research on augmented reality. Immersive digital technologies are used to enhance learning outcomes across affective, cognitive, behavioral, and engagement domains. This technology helps improve students' affective skills, such as environmental awareness, ecological empathy, positive attitudes toward conservation, and connectedness to nature. Game-based and narrative-based learning contribute to increased affective engagement and learning motivation. In the learning process, immersive digital technology is facilitated by contextual learning designs, such as experiential, inquiry-based, and situated learning. This review shows that immersive digital technologies in ecology and environmental education depend on the learning approach and objectives, enabling these technologies to support learning outcomes such as cognitive, affective, behavioral, and engagement. In addition, learning outcomes are influenced by immersive modality and learning approach. Keywords: augmented reality, virtual reality, virtual field trips, ecology education, environmental education.